CONSIDERATIONS ON SEXUALITY AND SEXUAL EDUCATION OF PERSONS WITH AUTISTIC SPECTRUM DISORDERS - Vieira Ottoni, Ana Carla; Bortolozzi Maia, Ana Claudia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
Autism Spectrum Disorder (ASD) is a developmental disorder, characterized by deficits in social communication and restricted/repetitive interests or behaviors. This work, focused on the levels of TEA that require less support, previously described as Asperger's Syndrome and here denominated TEA/SA, presents a theoretical revision on the sexuality of this population. Such sexuality is often invisible, the right of access to information and sexual experiences commonly denied, and there is vulnerability to abuse and violence. Studies indicate that deficits in social skills, communication, restricted and repetitive interests and hypersensitivity are possible limiting factors of sexual development. Some data point to the identification of sexual desires focused especially on solitary experiences of sexuality and less frequent sexual practices compared to the population. The difficulties of parents and professionals to talk about sexuality were highlighted, and an efficient program of sexual education for people with TEA/SA was appointed as a protective factor for a satisfactory development and reduction of victimization, including this intervention important aspects such as the use of accessible, direct and clear language; the systematic teaching of social skills; family and professional orientation. The literature review was important to clarify the issue and support the development of sexual education proposals for this population, without omitting, of course, the needs of the people with TEA/SA.
Keywords: Autism spectrum disorder; Asperger Syndrome; Sexuality; Sexual education